Long-term mineralogical and geochemical evolution of sulfide mine tailings under a shallow water cover. (June 2015) - Moncur, Michael C.; Ptacek, Carol J.; Lindsay, Matthew B.J.; Blowes, David W.; Jambor, John L.
Graphical abstract: Highlights: Sulfide-rich mine tailings stored under a 1 m water cover for six decades. Sulfide-mineral oxidation limited to 6 cm in sub-aqueous tailings. Corresponding sub-aerial tailings exhibited oxidation to a depth of 60 cm. Dissimilatory sulfate reduction limits dissolved metals in sub-aqueous tailings. Secondary sulfide minerals precipitating in reduced zones of sub-aqueous tailings. Abstract: The long-term influence of a shallow water cover limiting sulfide-mineral oxidation was examined in tailings deposited near the end of operation in 1951 of the former Sherritt-Gordon Zn–Cu mine (Sherridon, Manitoba, Canada). Surface-water, pore-water and core samples were collected in 2001 and 2009 from above and within tailings deposited into a natural lake. Mineralogical and geochemical characterization focused on two contrasting areas of this deposit: (i) sub-aerial tailings with the water table positioned at a depth of approximately 50 cm; and (ii) sub-aqueous tailings stored under a 100 cm water cover. Mineralogical analyses of the sub-aerial tailings showed a zone of extensive sulfide-mineral alteration extending 40 cm below the tailings surface. Moderate alteration was observed at depths ranging from 40 to 60 cm and was limited to depths >60 cm. In contrast, sulfide-mineral alteration within the submerged tailings was confined to a <6 cm thick zone located immediately below the water-tailings interface. This narrow zone exhibited minimal sulfide-mineral alteration relative to the sub-aerial tailings. Sulfur K-edge X-ray absorption near edge structure (XANES) spectroscopy showed results that were consistent with the mineralogical investigation. Pore-water within the upper 40 cm of the sub-aerial tailings was characterized by low pH (1.9–4.2), depleted alkalinity, and elevated SO4 and metal concentrations. Most-probable number (MPN) enumerations revealed abundant populations of acidophilic sulfur-oxidizing bacteria within these tailings. Conversely, pore-water in the sub-aqueous tailings was characterized by near-neutral pH, moderate alkalinity, and relatively low concentrations of dissolved SO4 and metals. These tailings exhibited signs of dissimilatory sulfate reduction (DSR) including elevated populations of sulfate reducing bacteria (SRB), elevated pore-water H2 S concentrations, and strong δ 34 S-SO4 and δ 13 C-DIC fractionation. Additionally, mineralogical investigation revealed the presence of secondary coatings on primary sulfide minerals, which may serve as a control on metal mobility within the sub-aqueous tailings. Results from this study provide critical long-term information on the viability of sub-aqueous tailings disposal as a long-term approach for managing sulfide-mineral oxidation.